DAYA TARIK WISATA FESTIVAL BUDAYA PERAHU BAGANDUANG DI LUBUK JAMBI KABUPATEN KUANTAN SINGINGI - Kholil, Irfan; Rifiyan, Andi M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research purposed to get know how culture festival perahu baganduang can improve tourist arrivals and how role the progress to tourism in lubuk jambi regency kuantan singingi. This research use metode descriptive qualitative to examine the issues raised. The source in this research is community leaders, stakeholders competent, Department of Culture, Tourism, regency Kuantan Singingi, and the executive committee culture festival perahu baganduang and tourist at festival perahu baganduang. While data collection techniques in this research use method observation, interviews, and documentation. Based on the research results has done, tourist culture perahu baganduang in area lubuk jambi still more not by the outside people, only area regency kuantan singingi has know festival perahu baganduang because resource, accessibility, facilities and infrastructure has a unique not managed maximal. Because development costs Insufficient which led to a promotion to be limited.Keywords: tourist attraction, culture festival, perahu baganduan